Extratos de mostarda-da-índia no controle de oídio em pepino e na indução de fitoalexina em soja - Piacentini, Patrícia de Oliveira (2014)
Cucumber (Cucumis sativus L.) belonging to the family of Cucurbits, is a plant originating in Asia, being cultivated in Indian for over 3000 years. Powdery mildew, caused by the fungus Podosphaera fuliginea, is one of the diseases that most affects the culture of cucumber, primarily in protected environments. The disease is favored in places or periods where the temperature is around 20 to 25°C and low humidity. Advocating the use of alternative products effective management of disease, aimed to test the efficiency of different methods of obtaining extracts of Indian mustard (Brassica juncea) in the control of powdery mildew in cucumber and production of phytoalexin. The in vivo experimente was conducted in a greenhouse in Federal Technological University of Paraná, with the use of experimental design 3x5 (three methods for obtaining extracts x five doses) with four repetitions per treatment. The extracts used were the aqueuos, macerated and infusion in doses of 0 (water only), 3, 6, 9, and 12%. Cucumber seeds cultivar Caipira were sown in trays containing substrate and after seven days have been transplanted in pots with soil sifted forest. The first application of the extracts occurred 24 hours before exposure on plants to pots with plants with high severity of the disease. The remaining applications were carried out with weekly interval, totaling five applications. At the same time, was evaluated the severity of powdery mildew in four sheets previously marked. The phytoalexin test was conducted in soybean cotyledons, where 50 μL were applied the methods of obtaining the extracts at a dose of 12% and 50 μL of positive and negative control that were the solution of Saccharomyces cerevisiae (yeast organic) and water, respectively. The extracts of Indian mustard have been effective in the control of powdery mildew in cucumber, there is no significant difference between the different methods of obtaining the extracts. On the other hand, it was noted dose effect on severity of powdery mildew, especially if the dose of 12% by controlling the disease severity in 77,95% and 81,16% in the first and second cultivation, respectively. In soybean cotyledons, the extract of Indian mustard, obtained by methods aqueous, infusion and maceration, induced the synthesis of phytoalexin gliceollin, including in relation to positive and negative treatments.